Prostate cancer susceptibility and growth linked to Y chromosome genes - Patel, Riddhi (Front Biosci (Elite Ed), 2018)
The role of Y chromosome in prostate cancer progression and incidence is not well known. Among the 46 chromosomes, Y chromosome determines the male gender. The Y chromosome is smaller than the X chromosome and contains only 458 genes compared to over 2000 genes found in the X chromosome. The Y chromosome is prone to high mutation rates, created exclusively in sperm cells due to the highly oxidative environment of the testis. Y chromosome harbors epigenetic information, which affects the expression of genes associated with the incidence and progression of prostate cancer. In this review, we focus on Y chromosome related genetic abnormalities, likely to be involved in the development and progression of prostate cancer.